2009
DOI: 10.1093/pasj/61.sp1.s337
|View full text |Cite
|
Sign up to set email alerts
|

Suzaku Observations of Metallicity Distribution in the Intracluster Medium of the NGC 5044 Group

Abstract: The metallicity distribution in the intracluster medium of the NGC 5044 group was studied up to 0.3 $r_{180}$ using the XIS instrument aboard the Suzaku satellite. The abundances of O, Mg, Si, S, and Fe were measured with high accuracy. The region within a radius of 0.05 $r_{180}$ from the center shows approximately solar abundances of Mg, Si, S, and Fe, while the O$/$Fe ratio is about 0.5–0.6 in solar units. In the outer region, the Fe abundance gradually drops to 0.3 solar. The radial abundance profiles of M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
50
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(58 citation statements)
references
References 47 publications
8
50
0
Order By: Relevance
“…This suggests that the higher abundance of Fe in the former is not simply due to a higher SNIa rate-which would skew the abundance pattern-but, in the context of the models described above, may be explained by either more efficient removal of enriched gas or a higher average inflow rate of relatively unenriched gas in the latter. In general, the level and pattern of abundances for other elliptical galaxies observed with Suzaku are near solar (Matsushita et al 2007;Tawara et al 2008;Komiyama et al 2009;Sato et al 2009;Hayashi et al 2009)-similar to what we report here for NGC 4649, indicating that our simple models may be widely applicable in accounting for the origins of ISM metals in elliptical galaxies (although with somewhat lower abundances than typical of X-ray luminous ellipticals, NGC 4649 may be a somewhat extreme case). A more thorough analysis that compares and contrasts elliptical galaxy ISM abundances in the context of their environments and intrinsic properties is beyond the scope of this paper, but is currently being pursued.…”
Section: Ngc 4472 and Other Ellipticals (Briefly) Revisitedsupporting
confidence: 83%
“…This suggests that the higher abundance of Fe in the former is not simply due to a higher SNIa rate-which would skew the abundance pattern-but, in the context of the models described above, may be explained by either more efficient removal of enriched gas or a higher average inflow rate of relatively unenriched gas in the latter. In general, the level and pattern of abundances for other elliptical galaxies observed with Suzaku are near solar (Matsushita et al 2007;Tawara et al 2008;Komiyama et al 2009;Sato et al 2009;Hayashi et al 2009)-similar to what we report here for NGC 4649, indicating that our simple models may be widely applicable in accounting for the origins of ISM metals in elliptical galaxies (although with somewhat lower abundances than typical of X-ray luminous ellipticals, NGC 4649 may be a somewhat extreme case). A more thorough analysis that compares and contrasts elliptical galaxy ISM abundances in the context of their environments and intrinsic properties is beyond the scope of this paper, but is currently being pursued.…”
Section: Ngc 4472 and Other Ellipticals (Briefly) Revisitedsupporting
confidence: 83%
“…Amongst the few objects in common between the ASCA and XMM-Newton samples are A3112 (Finoguenov et al 2000) and A2052 (Finoguenov et al 2001) for which ASCA data found Si/Fe radial gradients and XMM-Newton derived flat Si/Fe profiles. Recent analysis of SUZAKU data (Sato et al 2007b(Sato et al , 2009aKomiyama et al 2009) on a handful of groups and poor clusters leads to Si/Fe profiles that are consistent with being constant out to at least 0.1 r 180 and in some instances to 0.2 r 180 . Since at 0.1 r 180 the average Fe abundance excess is about 1/2 of what it is within 0.03 r 180 (Leccardi & Molendi 2008a), this seems to rule out the possibility that the transition from central excess to flat Fe profile might be associated with a change in SN type mix.…”
Section: Discussionmentioning
confidence: 87%
“…In the outer regions, 0.1-0.2 r 180 , Fe abundances of 0.4-0.5 solar appear to be universal with no temperature dependence. We calculated the weighted average of the Fe abundances, dividing clusters except for A426 and A1656 according to whether they [12], AWM7 cluster [13], Abell 262 [14], the Perseus cluster [15], the NGC 5044 group [16], the NGC 1550 group [17], HCG 62 [18], the NGC 507 group [19], and the Fornax cluster [20,21]. SN II yields by Nomoto et al [22] refer to an average of the Salpeter initial mass function.…”
Section: The Radial Profiles Of the Fe Abundancesmentioning
confidence: 99%
“…However, the IMLRs of the NGC 5044 group is constant from 0.1 r 180 to 0.3r 180 , and at 0.3 r 180 , the IMLR of the NGC 5044 group is nearly an order of magnitude larger than that of the Fornax cluster. [19], HCG 62 group [18], NGC 5044 group [16], and a fossil group, NGC 1550 [17]. The weighted average of relaxed clusters with a cD galaxy at their center observed with XMM [24] and the best-fit regression relations for groups of galaxies observed with Chandra [27] and cool-core groups observed with XMM [28] are also plotted.…”
Section: Radial Profiles Of the Metal-mass-to-light Ratiosmentioning
confidence: 99%
See 1 more Smart Citation